Social Dynamics and Peer Perceptions: Early Marriage and Premarital Pregnancy Among Adolescents in Tana Toraja - Umrah, Andi Sitti; Dahlan, Andi Kasrida (Media Publikasi Cendekia Indonesia, 2025)
The issue of early marriage and premarital pregnancy among adolescents has become a critically important topic, attracting serious attention at global, national, and local levels. This study aims to (i) explore peer dynamics in shaping adolescents' perceptions of early marriage and premarital pregnancy and (ii) analyze the influence of peers on adolescent decision-making regarding early marriage, premarital pregnancy, prevention, and education. This research employs a mixed-method approach (qualitative-quantitative). The study was conducted in Tana Toraja Regency in 2024. The population and sample consist of female adolescents aged 15–18 years. A stratified random sampling technique was used to select 168 respondents. Meanwhile, for the qualitative phase, 20 young women under the age of 18 were interviewed as affected individuals, examining the health, educational, and social impacts of early marriage and premarital pregnancy. Qualitative data collection was conducted through interviews and focus group discussions, whereas quantitative data were gathered via the distribution of questionnaires. Data analysis was conducted qualitative analysis through Nvivo software and quantitative analysis using Pearson correlation test and multiple linear regression. The findings indicate that peer influence plays a significant role in shaping adolescents’ perceptions of early marriage and premarital pregnancy. Statistical analysis using Pearson’s correlation test revealed a positive correlation between peer influence and adolescents’ perceptions of early marriage (r = 0,71) and premarital pregnancy (r = 0,73). Further analysis using multiple linear regression showed an R² value of 0,504, suggesting that approximately 50,4% of the variance in peer influence can be explained by the variables studied, indicating a substantial impact, particularly on perceptions of early marriage and premarital pregnancy. Overall, peer influence is significantly shaped by perceptions of early marriage and premarital pregnancy, underscoring the importance of social factors in shaping adolescent decisions regarding social and educational issues.